Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12991-021-00378-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of risk factors associated with suicidal ideation after stroke

Abstract: Background Over the past decade, increasing attention has been paid on post stroke suicide (PSS), which is one of complications of stroke. The rates of stroke and suicide are relatively high, especially in Asian populations. Thus, a deeper understanding of the prevalence and epidemiological impact of suicide after stroke is urgently needed. Clinical diagnosis and prevention of PSS are at the incipient stage, but the risk factors responsible for the occurrence of PSS in different regions and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Suicide is the most serious consequence of depression, where the prevalence of depression is about 2 to 9% ( 23 ). A Meta-analysis showed that the type of mental disorder most strongly associated with suicide attempts was depressive disorder ( 24 ). According to Eriksons theory of psychological development, college students are at a critical stage of rapid physical and mental development and are vulnerable to psychosocial factors ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Suicide is the most serious consequence of depression, where the prevalence of depression is about 2 to 9% ( 23 ). A Meta-analysis showed that the type of mental disorder most strongly associated with suicide attempts was depressive disorder ( 24 ). According to Eriksons theory of psychological development, college students are at a critical stage of rapid physical and mental development and are vulnerable to psychosocial factors ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PSD are at a higher risk of short-and long-term mortality (9,10). Additionally, PSD may be associated with a higher probability of cognitive impairment (11), an elevated risk of suicide (12), increased hospitalization costs (13), a greater risk of falls (14), and a lower quality of life than stroke survivors without PSD (15)(16)(17). Advanced age, female sex, history of depression, left hemispheric stroke, more severe disease, and genetic predisposition (e.g., apolipoprotein E) have been linked to the development of PSD (1).…”
Section: Introductionmentioning
confidence: 99%